From fun to fraught: marketing to kids and regulating "risky foods" in Canada. (2nd January 2020) - Elliott, Charlene
ABSTRACT: In an era of industrialized food production, ultra-processed foods, "Big Food" marketing, and growing obesity rates, food has come to be framed as an object of risk – and as an object of regulation. Such reframing has fascinating implications related to issues of responsibility and decision making, especially when it comes to children's food. This article probes the relationship between representation, regulation and "risky" consumption with respect to children's food. I examine how child-targeted foods become framed as "risky" and what counts as "risky" food messaging under Health Canada's commitment to restrict the marketing of unhealthy foods to children. Detailing the tension between food as a risk object and food as a child object, I suggest how issues of semantic provisioning and the politics of the unseen work to complicate and destabilize the (seemingly) straightforward process of prohibiting unhealthy food marketing to children.